At the edges of sleep : moving images and somnolent spectators - Ma, Jean, 1972- (University of California Press, 2022)
"Many recent works of contemporary art, performance, and film turn a spotlight on sleep, wresting it from the hidden, private spaces to which it is commonly relegated. At the Edges of Sleep considers sleep in film and moving image art as both a subject matter to explore onscreen and a state to induce in the audience"--